Double Knockout of Peroxiredoxin 4 (Prdx4) and Superoxide Dismutase 1 (Sod1) in Mice Results in Severe Liver Failure. (27th June 2018) - Homma, Takujiro; Kurahashi, Toshihiro; Lee, Jaeyong; Nabeshima, Atsunori; Yamada, Sohsuke; Fujii, Junichi
Abstract : Mice that are deficient in superoxide dismutase 1 (Sod1), an antioxidative enzyme, are susceptible to developing liver steatosis. Peroxiredoxin 4 (Prdx4) catalyzes disulfide bond formation in proteins via the action of hydrogen peroxide and hence decreases oxidative stress and supports oxidative protein folding for the secretion of lipoproteins. Because elevated reactive oxygen species induce endoplasmic reticulum stress, this negative chain reaction is likely involved in the development of nonalcoholic fatty liver diseases and more advanced steatohepatitis (NASH). In the current study, we generated Prdx4 and Sod1 double knockout (DKO; Prdx4 −/y Sod1 −/− ) mice and examined whether the combined deletion of Prdx4 and Sod1 aggravated liver pathology compared to single knockout and wild-type mice. The secretion of triglyceride-rich lipoprotein was strikingly impaired in the DKO mice, leading to aggravated liver steatosis. Simultaneously, the activation of caspase-3 in the liver was observed. The hyperoxidation of Prdxs, a hallmark of oxidative stress, occurred in different isoforms that are uniquely associated with Sod1 −/− and Prdx4 −/y mice, and the effect was additive in DKO mouse livers. Because DKO mice spontaneously develop severe liver failure at a relatively young stage, they have the potential for use as a model for hepatic disorders and for testing other potential treatments.